Generative Design applied to Cloud Modeling - Vaisman Muniz, Carlos Eduardo; Santos, Wagner Luiz Oliveira dos (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2021)
Geometric modeling has recently leveraged the power of Generative Design. Generative Design can be seen as a framework in which models can be generated by systematically exploring a space of shapes generated by recombination of parametric shape descriptors. In this work, we explore the use of Generative Design for modeling 3D clouds. Clouds are usually modeled in Computer Graphics as voxelized models by using a combination of implicit and procedural techniques. Hence, they are described by a large number of parameters. Although these parameters usually include parameters that define a combination of scalar fields, noise functions and affine transforms, the controlled use of such parameters is rather complex. How to tune them up to obtain a plausible result is not obvious. We propose a method based on generative design combined with Machine Learning to produce families of cloud shapes automatically. Our generative design method is based on an evolutionary approach that generates instances of plausible 3D cloud shapes by optimizing a fitness function that measures the likelihood of a shape be a cloud. As the manual design of a fitness function is also quite complex, we propose using a Convolutional Neural Network to learn the fitness of arbitrary 2D views of the generated clouds. We perform several experiments that confirm the viability of the proposed method compared to manually modeled clouds.